2017
DOI: 10.12693/aphyspola.132.770
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Applied Current Density on the Structural and Magnetic Properties of the Electrodeposited Cobalt-Nickel Alloy Thin Films

Abstract: In this study, cobalt-nickel (Co-Ni) alloys were deposited electrochemically onto aluminum substrates under applied current densities of 103.8, 138.4, 173 and 207.6 A m −2 . Influence of the applied current density on the structural and magnetic properties of the Co-Ni alloys was investigated. The bath for Co-Ni alloys deposition was composed of 0.08 mol l −1 CoSO4·7H2O, 0.2 mol l −1 NiCl2·6H2O, 0.1 mol l −1 NiSO4·6H2O and 0.25 mol l −1 H3BO3. The electrochemical investigation of Co-Ni alloys was completed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…4,5) This composition-modulated Co-Ni laminated plating is available to produce by periodically varying stirring conditions during film formation in a single bath. Many of the studies [6][7][8][9][10][11][12] have been reported on the plating films consisted of the conventional metal multilayer films, but laminated structure producing required lamination in the plural different tanks or pulse electric plating as well as due to complicated manufacturing process, so that they are difficult to be put into industrial practice. In addition, there are many studies on the thickness of the constituent layers at the nanometer level, but there are few reports on thick films laminated with micrometer-level layers.…”
Section: Pp 426-432; J-stage Advance Published Date: August 23 2019)mentioning
confidence: 99%
“…4,5) This composition-modulated Co-Ni laminated plating is available to produce by periodically varying stirring conditions during film formation in a single bath. Many of the studies [6][7][8][9][10][11][12] have been reported on the plating films consisted of the conventional metal multilayer films, but laminated structure producing required lamination in the plural different tanks or pulse electric plating as well as due to complicated manufacturing process, so that they are difficult to be put into industrial practice. In addition, there are many studies on the thickness of the constituent layers at the nanometer level, but there are few reports on thick films laminated with micrometer-level layers.…”
Section: Pp 426-432; J-stage Advance Published Date: August 23 2019)mentioning
confidence: 99%
“…Cobalt-nickel (CoNi) alloys are high quality engineering materials having high strength, good wear resistance, corrosion resistance, hardness, nuclear power systems, thermal conductivity, electrocatalytic and magnetic properties [1][2][3][4]. It is known that CoNi alloys have excellent magnetic properties and also, they are superior to pure metals [5].…”
Section: Introductionmentioning
confidence: 99%